SEQUENTIAL TARGET EFFECTS IN FORCED-CHOICE PRIME VISIBILITY TESTS: IMPLICATIONS FOR UNCONSCIOUS PRIMING RESEARCH - Petrova, Anna; Kuznetsov, Ivan; Volkova, Maria (International Research Journal of Sociology, Psychology and Anthropology, 2024)
Unconscious processing of visual stimuli is a crucial area of study, and it is essential to ensure that the processing is indeed unconscious. This study explores the methods for ascertaining unconscious processing, including subjective reports and the combination of subjective and objective measures. Blindsight, a phenomenon in which individuals exhibit abovechance accuracy in identifying "undetected" stimuli, even though they claim not to see them, serves as a prominent example. While some researchers argue that blindsight represents severely degraded processing, many others contend that it is evidence of unconscious visual processing. This paper delves into the subjectivity of reports in indicating unconsciousness to visual stimuli and explores the implications of blindsight for the understanding of unconscious processing.